2015
DOI: 10.1155/2015/682397
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Complementary and Alternative Medicine among Lebanese Adults: Results from a National Survey

Abstract: Objective. To examine the prevalence and correlates of Complementary and Alternative Medicine (CAM) use in Lebanon. Methods. A cross-sectional survey was conducted through face to face interviews on a nationally representative sample of 1,475 Lebanese adults. The survey questionnaire explored the sociodemographic and health related characteristics as well as the types and modes of CAM use. The main outcome in this study was the use of CAM during the last 12 months. Results. Prevalence of CAM use was 29.87% wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 47 publications
7
62
2
Order By: Relevance
“…The most common reason of using UM is treating illness which similar to other studies [10,12,13,19] . In this study showed similar previous studies [20] the young adult showed positive attitude about UM. Conclusions, Many young adult used and would consider using different modalities of UM for treatment of illness and wellbeing.…”
Section: Discussionsupporting
confidence: 92%
“…The most common reason of using UM is treating illness which similar to other studies [10,12,13,19] . In this study showed similar previous studies [20] the young adult showed positive attitude about UM. Conclusions, Many young adult used and would consider using different modalities of UM for treatment of illness and wellbeing.…”
Section: Discussionsupporting
confidence: 92%
“…One of the most broadly used definitions, found in numerous studies is the definition of the WHO [12] that proposes to call them complementary/alternative medicine [CAM] as for its use regarding biomedicine. As Naja et al [13] pointed out the United States National Center for CAM therapies divides complementary and alternative medicine into four categories: mind-body system; manipulative and body-based practices; energy medicine and biologically based practices.…”
Section: The Offer Of Workhops Since New Volunteerismmentioning
confidence: 99%
“…This practice is widely used worldwide; 80% in the African population and 42% among the Americans had used it at least once [2]. It was reported as well in many countries including the developing countries, Mediterranean region and Islamic societies; In Palestine, the use of at least one type of (CM) was 73%; In Lebanon, a survey documented the use of (CM) in about 30% of adults [3]; In Egypt it was found that 77.5% of adults reported the use of CM [4]. Many patients with chronic illnesses including cancer use (CM) during and after treatment and the reasons included doubts concerning the effectiveness of conventional treatment, dissatisfaction with the medical care and attempts to improve one's physical and emotional health [5].…”
Section: Introductionmentioning
confidence: 99%